Measuring Success of Youth Livelihood Interventions : A Practical Guide to Monitoring and Evaluation - Hempel, Kevin (World Bank, Washington, DC, 2016)
Programs to actively support young people's employment prospects have existed for decades in industrialized countries; however, they are relatively new in developing nations. In a broad sense, youth livelihood interventions support young people's means to earn a living, and include training, public service, youth entrepreneurship, and financial services. More narrowly, many practitioners define youth livelihood programs as activities targeting particularly vulnerable and marginalized groups in the informal economy, with a specific focus on self-employment. This guide adopts the broader definition and includes workforce development for the formal sector. This is an introductory guide written for practitioners with no or very limited knowledge about impact evaluation or quantitative research methods, but who nonetheless care about demonstrating the true results of their work. It speaks to program managers and local monitoring and evaluation (M&E) officers across all types of organizations active in the youth livelihood field: local and international NGO's, local and national government officials, and bilateral and multilateral donors. Given the diversity of backgrounds and experiences among practitioners, it is impossible to tailor this guide to everyone equally well. However, we have tried to provide a comprehensive discussion of evaluation methods for youth livelihood interventions so that readers can identify the sections most relevant to their own interests and needs. With this guide, we aim to equip readers with the basic set of concepts and tools needed to make informed decisions about how to best evaluate their programs. We seek to provide a clear understanding of the variety of evaluation options available and the considerations that will allow practitioners to choose the most appropriate one based on learning objectives and operational context. Moreover, we describe how to manage an impact evaluation if it is the assessment method of choice. Our overarching goal is to strengthen the foundation of sound programming and policymaking by increasing the number of quality evaluations in the youth livelihood field, thereby facilitating the scale-up and replication of successful interventions.